PID controller using rapid control prototyping techniques - Odair A. Trujillo; Nicolás Toro-García; Fredy E. Hoyos (International Journal of Electrical and Computer Engineering (IJECE), 2019)
To analyze the performance of the PID controller in a buck type converter implemented in real time. We begin by designing a continuous controller using the analytical method for calculating PIDs. Pulse width modulation is then used and bifurcation diagrams analyzed to reveal some problems of switching and sampling time. The model converter is then implemented with a PID controller in dSPACE. The experimental results provide detailed requirements of sampling frequency and switching speed, and show the performance of the PID controller. Converters are used in power generation solar systems and conmuted power sources for feed telecommunication devices, smart grids, and other applications.